Assessment and use of drug information references in Utah pharmacies - Moorman KL; MacDonald EA; Trovato A; Tak CR (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Objective: To determine which drug references Utah pharmacists use most frequently. To determine which types of drug information questions are most commonly asked, and whether Utah pharmacists have access to adequate references to respond to these questions. Methods: A 19-question survey was created using Qualtrics, LLC (Provo, Utah) software. An electronic survey link was sent to 1,431 pharmacists with a valid e-mail address listed in the Department of Professional Licensing database. Questions focused on available references in the participant's pharmacy, how current the references are, and the participant's use of the references. Surveys were analyzed for participants practicing in either community or hospital pharmacies in the state of Utah. Results: A total of 147 responses were included in the analysis. Approximately 44% of respondents practiced in the community, and 56% practiced in a hospital setting. The most commonly used references by Utah pharmacists are Micromedex, Lexicomp, UpToDate, Clinical Pharmacology, and Drug Facts & Comparisons. Pharmacists in the community frequently receive questions related to adverse drug reactions, drug interactions, and over-the-counter medications. Pharmacists in the hospital frequently receive questions relating to dosage and administration, drug interactions, and adverse drug reactions. About 89% of community pharmacists and 96% of hospital pharmacists feel available references are adequate to answer the questions they receive. Conclusions: Utah pharmacists generally use large reference suites to answer drug information questions. The majority of pharmacists consider the references available to them to be adequate to answer the questions they receive.